Neuvostoliitto muistoissa ja mielikuvissa - Helle, Anna; Koivunen, Pia (Suomalaisen Kirjallisuuden Seuran Toimituksia, 2022)
The volume Remembered and Imagined Soviet Union addresses memories, conceptions, and images relating to the Soviet past from the perspective of cultural memory. The book explores how the Soviet Union has been recalled and how it has been depicted in cultural products like literature, museum exhibitions, art and the media. Instead of trying to say what the Soviet Union was, the book analyses the ways in which Finns, Russians and Estonians have viewed the Soviet past at different times. The book answers the following questions: What is remembered about the Soviet past? How has the country been represented in various cultural texts? What is forgotten or not talked about? The book consists of chapters by scholars of history, literature and art studies. They look at key themes of the Soviet past in the framework of cultural memory, with topics including space conquest, the superiority of the hockey team, known as the "Red machine", political propaganda, and persecution of minorities.